Comparison of fracture risk using different supplemental doses of vitamin D, calcium or their combination: a network meta-analysis of randomised controlled trials - Zhi-Chao Hu; Zhen-Hua Feng; Jiang-Wei Xuan; Wen-Fei Ni; Li Tang; Qian Tang; Chang-Min Sang; Xiaobin Li; Zhi-Hao Shen; Li-Yan Shen; Ai-Min Wu (BMJ Open)
Objective Inconsistent findings in regard to association between different concentrations of vitamin D, calcium or their combination and the risk of fracture have been reported during the past decade in community-dwelling older people. This study was designed to compare the fracture risk using different concentrations of vitamin D, calcium or their combination.Design A systematic review and network meta-analysis.Data sources Randomised controlled trials in PubMed, Cochrane library and Embase databases were systematically searched from the inception dates to 31 December 2017.Outcomes Total fracture was defined as the primary outcome. Secondary outcomes were hip fracture and vertebral fracture. Due to the consistency of the original studies, a consistency model was adopted.Results A total of 25 randomised controlled trials involving 43 510 participants fulfilled the inclusion criteria. There was no evidence that the risk of total fracture was reduced using different concentrations of vitamin D, calcium or their combination compared with placebo or no treatment. No significant associations were found between calcium, vitamin D, or combined calcium and vitamin D supplements and the incidence of hip or vertebral fractures.Conclusions The use of supplements that included calcium, vitamin D or both was not found to be better than placebo or no treatment in terms of risk of fractures among community-dwelling older adults. It means the routine use of these supplements in community-dwelling older people should be treated more carefully.PROSPERO registration number CRD42017079624.